Especial skills in experienced archers - Nabavinik, M.; Abaszadeh, A.; Mehranmanesh, M.; Rosenbaum, D. A. (Journal of Motor Behavior, 2018)
Especial skills are skills that are distinctive by virtue of massive practice within the narrow contexts in which they are expressed. In the first demonstration of especial skills, Keetch, Schmidt, Lee, and Young (2005) showed that experienced basketball players are better at shooting baskets from the foul line, where they had massive amounts of practice, than would expected from their success at other locations closer to or farther from the basket. Similar results were obtained for baseball throwing. The authors asked whether especial skills hold in archery, a sport requiring less movement. If the emergence of especial skills depends on large-scale movement, one would expect archery to escape so-called especialism. But if the emergence of especial skills reflects a more general tendency for highly specific learning, experienced archers should show especial skills. The authors obtained evidence consistent with the latter prediction. The expert archers did much better at their most highly practiced distance than would be expected by looking at the overall function relating shooting score to distance. We offer a mathematical model to account for this result. The findings attest to the generality of the especial skills phenomenon.